Reference Values of Pulse Wave Velocity in Healthy Children and Teenagers - Reusz, George S.; Cseprekal, Orsolya; Temmar, Mohamed; Kis, Éva; Cherif, Abdelghani Bachir; Thaleb, Abddelhalim; Fekete, Andrea; Szabó, Attila J.; Benetos, Athanase; Salvi, Paolo (Hypertension (Dallas, Tex. 1979), 2010)
Carotid-femoral pulse wave velocity is an established method for characterizing aortic stiffness, an individual predictor of cardiovascular mortality in adults. Normal pulse wave velocity values for the pediatric population derived from a large data collection have yet to be available. The aim of this study was to create a reference database and to characterize the factors determining pulse wave velocity in children and teenagers. Carotid-femoral pulse wave velocity was measured by applanation tonometry. Reference tables from pulse wave velocities obtained in 1008 healthy subjects (aged between 6 and 20 years; 495 males) were generated using a maximum-likelihood curve-fitting technique for calculating SD scores in accordance with the skewed distribution of the raw data. Effects of sex, age, height, weight, blood pressure, and heart rate on pulse wave velocity were assessed. Sex-specific reference tables and curves for age and height are presented. Pulse wave velocity correlated positively (P<0.001) with age, height, weight, and blood pressure while correlating negatively with heart rate. After multiple regression analysis, age, height, and blood pressure remained major predictors of pulse wave velocity. This study, involving >1000 children, is the first to provide reference values for pulse wave velocity in children and teenagers, thereby constituting a suitable tool for longitudinal clinical studies assessing subgroups of children who are at long-term risk of cardiovascular disease.